A review of carbon-composited materials as air-electrode bifunctional electrocatalysts for metal–air batteries - Wang, Yan-Jie; Fang, Baizeng; Zhang, Dan; Li, Aijun; Wilkinson, David P; Ignaszak, Anna; Zhang, Lei; Zhang, Jiujun (Electrochemical energy reviews, 2018)
Metal–air batteries (MABs), particularly rechargeable MABs, have gained renewed interests as a potential energy storage/conversion solution due to their high specific energy, low cost, and safety. The development of MABs has, however, been considerably hampered by its relatively low rate capability and its lack of efficient and stable air catalysts in which the former stems mainly from the sluggish kinetics of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) and the latter stems from the corrosion/oxidation of carbon materials in the presence of oxygen and high electrode potentials. In this review, various carbon-composited bifunctional electrocatalysts are reviewed to summarize progresses in the enhancement of ORR/OER and durability induced by the synergistic effects between carbon and other component(s). Catalyst mechanisms of the reaction processes and associated performance enhancements as well as technical challenges hindering commercialization are also analyzed. To facilitate further research and development, several research directions for overcoming these challenges are also proposed.